2021
DOI: 10.3389/fmats.2021.700118
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Compaction and Deformation of Filling Gangue by Reducing Waste Gangue for Filling Mining

Abstract: The coal mining technology of fully mechanized solid filling is an efficient and green mining method that integrates “sediment reduction” and “emission reduction.” However, the discharge of wasted gangue and surface subsidence are controlled by the amount of wasted gangue used in filling mining and the compaction rate of gangue filled into a goaf, respectively. To increase the consumption of wasted gangue and reduce surface subsidence, mixed gangue composed of equal-quality washed gangue and crushed gangue is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…With the long-term sustained development of coal resources, the continuous underground coal mining activities have caused surface subsidence and accumulation of coal gangue waste, which has seriously affected coal mining and caused serious pollution to the living environment in mining areas 1 4 . Fill mining, as a green mining technology, utilises coal gangue underground for filling in order to reduce problems such as difficulty in accumulating coal gangue on the surface and pollution of the environment, to improve the recovery rate of coal resources and to control surface subsidence 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…With the long-term sustained development of coal resources, the continuous underground coal mining activities have caused surface subsidence and accumulation of coal gangue waste, which has seriously affected coal mining and caused serious pollution to the living environment in mining areas 1 4 . Fill mining, as a green mining technology, utilises coal gangue underground for filling in order to reduce problems such as difficulty in accumulating coal gangue on the surface and pollution of the environment, to improve the recovery rate of coal resources and to control surface subsidence 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…They found that as the particle size of gangue increases, the gangue particles are more susceptible to experiencing force chain instability and failure. Dong et al 28 , 29 proposed using both washed gangue and crushed gangue as solid filling materials. They employed a similar gradation method to prepare test samples and conducted combined compression tests to compare and analyze compression characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale and high-intensity mining activities and the utilization of coal resources have produced a large amount of solid waste of coal gangue [1][2][3], occupying a large number of land resources and polluting air, groundwater and soil, resulting in a series of ecological, environmental problems [4][5][6]. The coal gangue and water are mixed into a certain concentration of gangue slurry through the underground slurry preparation system, and the goaf caving zone is filled with adjacent grouting to realize the harmless disposal of coal gangue under the low interference condition of the working face [7,8].…”
Section: Introductionmentioning
confidence: 99%